Automatic analyzer for highly polar carboxylic acids based on fluorescence derivatization–liquid chromatography. (1st August 2014) - Todoroki, Kenichiro; Nakano, Tatsuki; Ishii, Yasuhiro; Goto, Kanoko; Tomita, Ryoko; Fujioka, Toshihiro; Min, Jun Zhe; Inoue, Koichi; Toyo'oka, Toshimasa
Abstract A sensitive, versatile, and reproducible automatic analyzer for highly polar carboxylic acids based on a fluorescence derivatization–liquid chromatography (LC) method was developed. In this method, carboxylic acids were automatically and fluorescently derivatized with 4‐(N, N‐dimethylaminosulfonyl)‐7‐piperazino‐2, 1, 3‐benzoxadiazole (DBD‐PZ) in the presence of 4‐(4, 6‐dimethoxy‐1, 3, 5‐triazin‐2‐yl)‐4‐methylmorpholinium chloride by adopting a pretreatment program installed in an LC autosampler. All of the DBD‐PZ‐carboxylic acid derivatives were separated on the ODS column within 30 min by gradient elution. The peak of DBD‐PZ did not interfere with the separation and the quantification of all the acids with the exception of lactic acid. From the LC‐MS/MS analysis, we confirmed that lactic acid was converted to an oxytriazinyl derivative, which was further modified with a dimethoxy triazine group of 4‐(4, 6‐dimethoxy‐1, 3, 5‐triazin‐2‐yl)‐4‐methylmorpholinium chloride (DMT‐MM). We detected this oxytriazinyl derivative to quantify lactic acid. The detection limits (signal‐to‐noise ratio = 3) for the examined acids ranged from 0.19 to 1.1 µm, which correspond to 95–550 fmol per injection. The intra‐ and inter‐day precisions of typical, highly polar carboxylic acids were all <9.0%. The developed method was successfully applied to the comprehensive analysis of carboxylic acids in various samples, which included fruit juices, red wine and media from cultured tumor cells. Copyright © 2014 John Wiley & Sons, Ltd.